(untitled) (Papeles, 2011)
From an epistemological approach, it is necessary to acknowledge the didactic system of mathematics teacher and differentiate it from the didactic system of the mathematics; in this way it is recognized that Mathematics Education fails to address the issues of Mathematics Teacher Education [MTE] and it is noticed the factual emergence of a new field of research. Some existence evidence of that research field are: the existence of some publications, the studies on education of pre-service and in-service mathematics teachers, or the activity of an academic community reflected in the specific treatment of the MTE’s problems in academic events or in the development of events focusing on the mathematics teacher education. The descriptive phenomenology of that field is defining by its specific objects. In this sense, approaches and research acknowledge some items like: the components of the mathematics teacher knowledge (MTK), the sources of MTK, the strategies of education for teachers of mathematics, or the knowledge of teacher trainers. This paper is one of the specific advances that the researching group RE-MATE can be evidenced in the process that has focused her efforts on behalf of research on Mathematics Teacher Education.